Implementation of Akad Salam in Improving Efficiency and Customer Satisfaction in Logistics and Trading Businesses in South Kalimantan - Husnah, Masnah Nur; Robi'in, M. (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
The high dynamics of the global economy necessitate adaptation by trading SMEs, while Islamic principles offer innovative instruments such as the Salam contract, which has the potential to stabilize cash flow but faces logistical and supply chain challenges. This study aims to analyze the implementation of the Salam contract in improving business efficiency and customer satisfaction, as well as examining the company’s strategies in overcoming resulting obstacles. The research utilizes a qualitative approach with a case study method at CV. Satui Jaya Makmur, involving in-depth interviews, observation, and documentation for data collection. The findings indicate that the Salam contract provides contractual certainty and transparency, significantly enhancing customer loyalty and satisfaction, alongside increased operational efficiency through cash flow stability. The company addresses logistical hurdles through strengthening supplier partnerships and predictive inventory management, supported by digital innovation and enhanced Sharia human resource competence. It is concluded that the implementation of the Salam contract is effective in achieving economic and ethical goals, providing a tangible contribution to strengthening Sharia-based SME management.